Defining the trials nurses' role in operationalising a medicinal cannabis clinical trial. Issue 3 (June 2022) - Razmovski-Naumovski, Valentina; West, Penny A.; Bellemore, Frances; Byfieldt, Naomi; Bellamy, Douglas; Chye, Richard; Clark, Katherine; Martin, Jennifer H.; Fazekas, Belinda; Phillips, Jane L.; Agar, Meera R.
Abstract: Background: With increasing use of medicinal cannabis for symptom management, clinical trials nurses need to consider the various legal, social, ethical, and interdisciplinary care issues of implementing these clinical trials, especially in a palliative care population. Aim: To define the trials nurses' role in operationalising a medicinal cannabis pharmacokinetic inpatient trial in an advanced cancer population. Methods: A qualitative, descriptive design incorporating case study methodology was used. Data were collected from minuted meetings, field notes, telephone, and email discussions involving trials nurses at two palliative care sites. Data were integrated and synthesised to identify the key considerations required to operationalise the trial and define the trials nurses' role. Findings: Three key considerations were identified: (i) Normalising the trial, (ii) Creating the environment to undertake the trial, and (iii) Managing the complexity. The trials nurses' role was explored through subthemes of these considerations including: their understanding of the purpose of the research and training in the protocol; organising inpatient resources, pharmacy requirements and managing the external scrutiny; participant recruitment, staffing requirements, safety, and supporting caregivers. Discussion: This study emphasises the multifactorial role of the trials nurses in managing a complex palliative care trial, and the importance of their early involvement and recognition as the vital link between all parties. Conclusion: Defining the trials nurses' role, within the confines of the protocol, the context of efficient nursing processes and ensuring a patient-centred approach enabled the operationalisation of a Phase I/II medicinal cannabis trial which will have global impact.